Profile of Blood Transfusion Requests from Hospitals to Bandung Blood Transfusion Unit, Indonesian Red Cross in 2011 - Syahla Nisaa Amalia; Najdwa Zamalek Dalimoenthe; Januarsih Iwan Rachman (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Blood transfusion as a part health services should be provided under appropriate indications and in a safe manner. In Indonesia, blood collection is run by the Blood Transfusion Unit of Indonesian Red Cross, where the blood is screened, processed into blood components, and finally distributed to hospitals. The purpose of this study was to describe the profile of blood transfusion requests from hospitals that do not have blood bank facility to the Bandung Blood Transfusion Unit, Indonesian Red Cross.Methods: A descriptive study was carried out using secondary data from Bandung Blood Transfusion Unit Indonesian Red Cross (UTD PMI Bandung). All blood request forms from hospitals during 2011 were collected and analyzed. Variables in this study were the amount of blood units, blood components, blood type, and indications of blood transfusion.Results: The number of blood units requested by hospitals were 35,841 units. The most blood units requested was in August 2011. The blood component requested was the packed red cell (61.1%), whole blood (17.4%), thrombocyte concentrate (10.6%), and fresh frozen plasma (7%). The total percentage of O, A, B and AB blood types were 36.1%, 28.6%, 27.5%, and 7.9% respectively. The most frequent indication for transfusion was anemia (61.7%), followed by surgery and other causes of bleeding. Conclusions: The total blood units requested by hospitals vary each month. The most blood component requested is Packed Red Cell and the type of blood is O blood type. The most frequent indication is anemia. DOI: 10.15850/amj.v2n3.519